SCREENING KELUHAN MUSKULOSKELETAL, PELAYANAN KESEHATAN FISIOTERAPI, PELATIHAN STRETCHING DAN SOSIALISASI FAKTOR RISIKO LOW BACK PAIN DAN POSISI KERJA ERGONOMIS PADA PETANI - Saraswati, P.A.S.; Antari, N.K.A.J.; Wibawa, A.; Thanaya, S.A.; Nugraha, M.H.S. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana MengabdiDO - 10.24843/BUM.2022.v21.i04.p13, 2023)
Occupational disease is a disease that has a specific cause or has a strong relationship with work, work tools, materials, processes and the work environment. Based on the situation analysis, the priority program is to help farmers to be able to work with the risk of musculoskeletal disease due to work as minimal as possible so that it does not interfere with productivity and cause disability. The prioritized programs include: screening for musculoskeletal complaints, stretching training, and physiotherapy services, as well as education about pain management that farmers can do at home independently. Based on the results of the service, it can be seen that the average age of subak farmers is 56 years with a total length of work reaching 16.5 years. Meanwhile, in terms of the value of the nordic body map, the average value was 30.6 and it was included in the low risk category of experiencing musculoskeletal disorders. This service activity went well where participants understood the risks of musculoskeletal disorders and how to stretch techniques. In addition, physiotherapy services have also been implemented in the form of providing interventions to farmers who experience low back pain, neck pain, tennis elbow, muscle spasms in the calves and arms. Provision of physiotherapy intervention is done by providing electrotherapy, manual therapy approaches such as massage, and exercise therapy. At the end of the session, the service team also conducted education about pain management that farmers could do at home independently, as well as socialization about low back pain and ergonomic work positions. Keywords: ergonomic, musculoskeletal, physiotherapy, stretching, farmers